Pengaruh Intensitas Penilaian Formatif terhadap Hasil Belajar IPA dengan Mengontrol Pengetahuan Awal Siswa - Muh. Ilyas Ismail (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
This study aims to determine the effect of intensity of formative assessment of science learning outcomes. Experimental studies with the study population was all students in grade V SD 03, and 05 am in East Jakarta, 80 samples of students, inferential statistical testing with the conclusion of the study are: (1). By controlling the initial knowledge of science students, there is a difference between the groups of students studying science are given formative assessment on each face to face with groups of students are given formative assessment on each standara competence (2). By controlling the students' prior knowledge of science, science learning outcomes of students who were given group of formative assessment on each face is higher than the group of students who were in the formative assessment of each competency standard.